A Comparative Approach to Fiscal Illusions: a Synthesis of the Conclusions from a Polish Study in Relation to New Ideas and Empirical Research in Selected Countries - Beata Guziejewska (Comparative Economic Research. Central and Eastern Europe, 2021)
This article examines fiscal illusions inpublic finance systems where decentralisation involving the introduction of an independent and autonomous component oflocal government funding brings new problems. It presents a synthesis ofthe findings from a Polish empirical study that set out to determine the types and extent offiscal illusion among Polish councillors, focusing on the qualitative aspects of the phenomenon. It also compares the findings with other streams of research and new approaches to fiscal illusion. The purpose ofthe article is to systematise the knowledge offiscal illusion based on selected empirical studies, to formulate proposals for practitioners and public decision-makers, and to highlight areas for future research to address. The article was prepared using adesk research approach and the author's own experienc-es and research perspective formed during the study offiscal illusions. The findings presented in the article corroborate its main thesis that a local government funding system based on intergovernmental transfers contributes tothe emergence and per-petuation of fiscal illusions.
Keywords: H70; H71; H77; 330; fiscal decentralisation; fiscal illusions; intergovernmental fiscal relations; local taxes